Impacts of pollution on coral bacterial and metabolites diversity across Dapeng Cove of South China sea - Feng Yan; Zhiguang Niu (Scientific Reports)
Abstract Coastal ecosystems are increasingly threatened by anthropogenic activities, including sewage discharge and tourism-related pollution, which alter microbial diversity and biochemical cycles. This study applied molecular techniques to examine the coral microbial diversity, and metabolite composition of seawater across five sites (A–E) in Dapeng Cove, South China Sea, to assess pollution impacts. Sites A and B, within the yacht tourism area, exhibited high microbial diversity, dominated by Synechococcus and Rhodobacteraceae, with minimal pollution effects. Site C, inside a domestic drainage channel, showed moderate pollution, with elevated nitrite (NO₂) and nitrate (NO₃) levels, microbial taxa linked to organic matter degradation, and increased hydroxy acids and indoles. Sites D and E, located in main sewage channels, experienced severe pollution, characterized by high salinity, low dissolved oxygen, and dominance of pollution-tolerant bacteria such as Exiguobacterium and Tepidibacter. Metabolite analysis revealed elevated fatty acyls, organonitrogen compounds, and amino acids at these sites, highlighting strong anthropogenic influence. Beta diversity analysis (NMDS and ANOSIM) confirmed distinct microbial community structures, while KEGG pathway analysis indicated shifts in metabolic functions, with enrichment in xenobiotic biodegradation and anaerobic respiration in sewage-impacted areas. These findings underscore the detrimental effects of wastewater discharge on microbial ecology and biochemical functions. Urgent interventions, including improved wastewater management and regular environmental monitoring, are recommended to mitigate pollution effects. Future research integrating multi-omics approaches is necessary to evaluate the long-term ecological consequences of pollution and climate variability on coastal microbial communities.